Plakophilin 3: a novel cell-type-specific desmosomal plaque protein - Schmidt, Ansgar; Langbein, Lutz; Franke, Werner (Differentiation, 2009)
Desomosomes are cell-cell adhesion structures of epithelia and some non-epithelial tissues, such as heart muscle and the dendritic reticulum of lymph node follicles, which on their cytoplasmic side anchor intermediate filaments at the plasma membrane. Besides clusters of specific transmembrane glycoproteins of the cadherin family (desmogleins and desmocollins), they contain several desmosomal plaque proteins, such as desmoplakins, plakoglobin, and one or more plakophilins. Using recombinant DNA and immunological techniques, we have identified a novel desmosomal plaque protein that is closely related to plakophilins 1 and 2, both members of the “armadillo-repeat” multigene family, and have named it plakophilin 3 (PKP3). The product of the complete human cDNA defines a protein of 797 amino acids, with a calculated molecular weight of 87.081 kDa and an isoelectric point of pH 10.1. Northern blot analysis has shown that PKP3 mRNA has a size of approximately 2.9 kb and is detectable in the total RNA of cells of stratified and single-layered epithelia. With the help of specific poly- and monoclonal antibodies we have localized PKP3, by immunofluorescence or immunoelectron microscopy, to desmosomes of most simple and almost all stratified epithelia and cell lines derived therefrom, with the remarkable exception of hepatocytes and hepatocellular carcinoma cells. We have also determined the structure of the human PKP3 gene and compared it with that of plakophilin 1 (PKP1). Using fluorescence in situ hybridization, we have localized the human genes for the three known plakophilins to the chromosomes 1q32 (PKP1), 12p11 (PKP2) and 11p15 (PKP3). The similarities and differences of the diverse plakophilins are discussed.